Unexpected Improvement of Liver Function by Intravenous Immunoglobulin in a Steroid-Experienced Severe Alcoholic Hepatitis - Tak, Kwon Yong (ACG Case Rep J, 2020)
Corticosteroid is the treatment of choice for severe alcoholic hepatitis; however, it can also lead to severe life-threatening infection. We report a 28-year-old severe alcoholic hepatitis patient who did not achieve a satisfactory improvement of the liver function by corticosteroid use but obtained a significant improvement of the liver function by intravenous immunoglobulin. Intravenous immunoglobulin was administered to control infection after prolonged corticosteroid usage; however, it led to an unexpected remarkable decrease in the serum total bilirubin level and restored the responsiveness to the additional corticosteroid used after the resolution of the infection.